Aplicación del prezi como herramienta didáctica para fortalecer el aprendizaje sobre la clasificación y disposición de los elementos químicos en la tabla periódica en los estudiantes del primer año de bachillerato paralelo “B”, de la unidad educativa “Dr. Manuel Agustín Cabrera Lozano” de la ciudad de Loja, periodo 2014 – 2015 - Alvarez Macas, Marlon Damian (2016)
The present thesis has the intention of implementing an educational tool to strengthen the learning about the classification and disposition of chemical elements in the Periodic Table and their properties with the use of Information Technology and Communication (ITC), particularly Prezi in the first year of baccalaureate, parallel "B" at "Dr. Manuel Cabrera Lozano” Educational Institution, the problem reside in the traditional teaching me thod used by the teacher, causes disinterest in students towards Chemistry learning, therefore it is important to study, analyze and put into practice the different concepts , theories and teaching tools in order to achieve significant learning. In this context, to the present research work the theme was raised: IMPLEMENTATION OF PREZI AS AN EDUCATIONAL TOOL TO STRENGTHEN LEARNING ABOUT THE CLASSIFICATION AND DISPOSITION OF CHEMICAL ELEMENTS IN THE PERIODIC TABLE IN THE STUDENTS OF THE FIRST YEAR OF BACCALAUREATE, PARALLEL "B", AT "DR. MANUEL AGUSTIN CABRERA LOZANO" EDUCATIONAL INSTITUTION OF LOJA CITY, PERIOD 2014-2015. The general objective is: To implement the Prezi as an educational tool to strengthen learning about the classification and disposition of chemical elements in the periodic table with the students of the first year of baccalaureate, parallel "B", at "Dr. Manuel Agustin Cabrera Lozano" Educational Institution of Loja City, Period 2014-2015. The inductive - deductive and analytical-synthetic methods were used. Besides, the Pearson’s correlation method was used. Bibliographical sources as books, websites, magazines and documents helped to develop in a scientific and orderly way the work. As well as the survey technique was applied and as instrument, the questionnaire in order to assess the effectiveness of the proposal made by the obtained data in the different workshops. After carrying out the discussion and analysis of the results, it was determined that students do not have a clear view about the classification and disposition of the chemical elements in the periodic table which causes the student does not develop significant learning in this subject. In addition, the use of technological tools by the teacher of the first year of baccalaureate, parallel "B", at "Dr. Manuel Agustin Cabrera Lozano" Educational Institution is limited, which determines that learning relative to the periodic table is rote characte